Two new species of Lathomicrus Jałoszyński (Coleoptera, Staphylinidae, Scydmaeninae) from Borneo - Jałoszyński, Paweł (Zootaxa, 2011)
Two new species of the previously monospecific ant-like stone beetle genus Lathomicrus Jałoszyński (Scydmaeninae, Cephenniini) are described: L. sarawakensis sp. n. and L. sabahensis sp. n., both from East Malaysia (Borneo). Diagnostic characters of the genus and new species are illustrated.